NEONATICIDE – LIGATURE STRANGULATION OF A NEWBORN - Biliana Mileva; Teodora Kiryakova; Dimitar Nikolov; Alexandar Alexandrov (Science & Research)

(untitled)
Introduction: Child murder dates back to the beginning of recorded history as children were intentionally killed or left to die for different reasons. It can be divided to three main groups – neonaticide, filicide or infanticide, depending on the age of the child and the perpetrator of the crime. Neonaticide refers to the homicide of a newborn within the first 24 hours after birth committed by the biological mother. Material and methods: Full forensic examination of the cadaver including external and internal examination was performed. The tests of Galen and Breslau were performed. Material for DNA-analysis was taken from the baby to compare with a suspected mother. Case presentation: A cadaver of a naked male baby was found in a trashcan. The cadaver was sent for autopsy in the Department of Forensic medicine and deontology in Sofia. The baby was born alive, mature and without any congenital malformations. The autopsy revealed the classical picture of ligature strangulation. Discussion and Conclusion: Women who commit neonaticide generally have made no plans for the birth or care of their child, as they often conceal the pregnancy throughout gestation from both family and friends. Therefore collaboration between different medical units and centers for psychosocial support is needed to find women at risk and to give them the needed help. Parents must be thoroughly educated about the extreme stress of the process of giving birth, and the further growth and development of the child.